Nicaragua : Poverty Assessment, Volume 1. Main Report - World Bank (Washington, DC, 2012)
Nicaragua is a small, open economy that is vulnerable to external and natural shocks. With an estimated Gross National Income (GNI) per capita of US$1000 in 2006, and a total population of 5.2 million, it is one of the poorest countries in Latin America. Forty six percent of the population lived below the poverty line in 2005 (while 15 percent lived in extreme poverty), and the incidence of poverty is more than twice as high in rural areas (68 percent) than in urban areas (29 percent). Nicaragua's social indicators also rank among the lowest in the region, commensurate with its relatively low per capita income level. Nicaragua's long-term development vision is set out in its National Development Plan (NDP), 2005-2009, which gives greater importance to economic growth than the strategy document that preceded it. This also serves as its second Poverty Reduction Strategy (PRS). The goals of the PRS incorporate the MDGs, and establish medium (2006-2010) to long term targets (2015). By 2005, the country had made satisfactory progress on meeting the PRS/MDG targets for reducing extreme poverty, increasing net primary enrollment, and reducing infant and child mortality. This National Development Plan is being revised by the new government that took office on January 2007, which has expressed interest in maintaining policy continuity in those areas that have shown progress and tackling pending development challenges. These include efforts to improve the country's growth performance while reducing poverty, macroeconomic stability as a necessary, although not sufficient, condition to stimulate growth, and reduce poverty, a special focus on social issues that impact the poorest, including the MDGs, and environmental sustainability. Programmatic priorities for the new administration include a renewed focus on poverty reduction using a multi-sector approach, implementing pragmatic solutions to the energy crisis for the short to medium term; expanding water and sanitation services with environmentally sustainable solutions; sharing economic growth more broadly to tackle hunger, malnutrition and poverty; placing greater emphasis on preventive health and continuing social protection programs; extending illiteracy programs and improving education services, and pursuing municipal decentralization, state modernization, and good governance.